2021
DOI: 10.3390/su13179717
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Firm Performance on Corporate Social Responsibility Practices: The Mediation Role of Corporate Governance in Ethiopia Corporate Business

Abstract: In today’s globalized economy, the corporate company faces ever-increasing competitive and social pressures. This paper aims to identify the impacts of firms’ performance on corporate social responsibility practices using the mediating roles of corporate governance evidence from Ethiopia’s corporate business. The impacts of firms’ performance on CSR and corporate governance as a mediator variable were studied using a sample of TIRET corporate companies, in the Amhara region, Ethiopia. The structural equation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 72 publications
3
28
0
2
Order By: Relevance
“…The one developed by Yang and Xia [54] highlighted pricing strategies for business sustainability. In addition, the model utilized by Ying et al [55] highlighted how restructuring, rebranding, and reconsideration of the current business should be done for efficiency. Lastly, the model considered by Ahmad et al [56] focused on service-related in accordance to sales.…”
Section: Research Conceptualization and Conjoint Designmentioning
confidence: 99%
“…The one developed by Yang and Xia [54] highlighted pricing strategies for business sustainability. In addition, the model utilized by Ying et al [55] highlighted how restructuring, rebranding, and reconsideration of the current business should be done for efficiency. Lastly, the model considered by Ahmad et al [56] focused on service-related in accordance to sales.…”
Section: Research Conceptualization and Conjoint Designmentioning
confidence: 99%
“…According to the hypothesis, CSR may be able to assist a firm in more effectively utilizing its resources, which may ultimately lead to greater commercial outcomes. This assumption, on the other hand, has not yet been shown beyond a reasonable doubt ( Ying et al, 2021 ). On the other hand, it seems that CSR has a complicated and ambiguous influence on performance, despite the fact that there is no specific support for this theory.…”
Section: Hypotheses Developmentmentioning
confidence: 97%
“…According to Krishnan, the occurrence of problems with an organization’s internal controls is far less likely to be connected with the presence of independent audit committees and audit committees that have financial knowledge. According to the findings of Ying et al (2021) , audit committees that have entirely independent members and at least one member with prior expertise in accounting or a related field have a negative correlation with financial restatements. Research conducted by Amin et al (2021) found that businesses that engage in fraudulent activity are more likely to have less independent audit committees.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Tanggung jawab sosial (CSR) termasuk suatu proses dalam menyatukan masalah terkait sosial, ekonomi, lingkungan, etika, hak hak asasi manusia, dan juga konsumen ke dalam aktivitas -aktivitas operasi bisnis perusahaan (Ying et al, 2021). CSR juga dapat berupa kesadaran perusahaan, kesuksesan sosial, atau bisnis yang berkelanjutan dan bertanggung jawab.…”
Section: Pendahuluanunclassified